Measuring Business Cycles - Wilson, Edwin B. (Quarterly Journal of Economics, 1950)
Journal Article Measuring Business Cycles Get access Edwin B. Wilson Edwin B. Wilson Office of Naval Research, Boston Branch Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 64, Issue 2, May 1950, Pages 311–318, https://doi.org/10.2307/1882698 Published: 01 May 1950